INFLUENCE OF ANTISEPTIC AND DESINFECTIVE PREPARATES ON FILMFORMING BACTERIA - Л. Л. Сіда; О. С. Воронкова; О. А. Сірокваша; Т. М. Шевченко; А. І. Вінніков (Mìkrobìologìâ ì Bìotehnologìâ. Мікробіологія і біотехнологія, 2015)
Aim. Study the efficacy of action of non-specific antibacterial agents on biofilm, formed by bacteria, isolated from the surface facilities, waste materials and the skin. Methods. Bacteria for research were isolated from the surfaces of stuff rooms, used instruments and also from the skin of 11 volunteers-patients hands. The ability to biofilmformation of isolated strains and their resistance to different antibacterial preparates under incubation with antiseptics and desinfectants were studied on plastic plates. Results. 179 strains were isolated and identified as: Bacillus spp. – 53.6%, S. epidermidis – 17.3%, S. аureus – 3.4%, E. coli – 12.3%, Acinetobacter spp. – 8.4%, Klebsiella spp., P. аeruginosa and Pseudomonas spp. – 1.1%, Enterobacteriaceae – 3,4%. 62% of isolates were received from the surfaces of stuff rooms, 12.3% – from the skin, 25.7% – from used instruments. It was shown, that 93.5% of S. epidermidis strains can form biofilm, that was one of the highest range between studied strains. After incubation of 72 h. biofilms of these strains with different antibacterial preparates for more than 60% of cultures shown absence of growth, for another – number of cells, that grew from homogenates, were no high as 103 CFU/ml. Maximal effect on inhibition of film growth was shown under use of disinfectant desactive-chlor. Under using of antiseptic chlorhexidin in concentration 5% sensitive to them in film were 84.6% of the strains. Conclusion. Under using of antibacterial preparates against 72 h. bacterial biofilm survivance of cells after 2 h. incubation of films with studied preparates was not more than 40%, that indicated on possibility of effective use of studied non-specific antibacterial agents against the spread of filmforming strains.